2005
DOI: 10.3748/wjg.v11.i8.1141
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of mast cells and TGF-β1 on the silymarin treatment for CCl4-induced hepatic fibrosis

Abstract: Anti-fibrotic and antiinflammatory effects of silymarin were associated with activation of hepatic stellate cells through the expression of TGF-beta1 and stabilization of mast cells. These results suggest that silymarin prevent hepatic fibrosis through suppression of inflammation and hypoxia in the hepatic fibrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 25 publications
9
56
0
1
Order By: Relevance
“…On the other hand, MT treatment was reported to decrease hepatic collagen content and hepatic fibrosis score in rats with carbon tetrachloride-induced liver fibrosis. Jeong et al (26) have demonstrated the anti-inflammatory effects, hepatic stellate cell activation, mast cell stabilization, and eventually antifibrotic feature of MT (26). Thus, when taken with the results of other studies, our findings suggest that UDCA, MT, or their combination have antifibrotic effects that involve the inhibition of oxidative hepatic injury.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…On the other hand, MT treatment was reported to decrease hepatic collagen content and hepatic fibrosis score in rats with carbon tetrachloride-induced liver fibrosis. Jeong et al (26) have demonstrated the anti-inflammatory effects, hepatic stellate cell activation, mast cell stabilization, and eventually antifibrotic feature of MT (26). Thus, when taken with the results of other studies, our findings suggest that UDCA, MT, or their combination have antifibrotic effects that involve the inhibition of oxidative hepatic injury.…”
Section: Discussionsupporting
confidence: 59%
“…However, its expression was reduced significantly with the administration of UDCA or MT or their combination. Previously, antifibrotic effects of UDCA and MT have been demonstrated (4,6,7,23,26,27). It was suggested that UDCA exerts an antifibrotic effect by reducing transforming growth factor-beta 1 expression, transforming growth factor type 1 receptor activation, and activation of the other components of the signaling pathways that were shown in the rat hepatic stellate cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic hydroxyprolin content was determined using the method described by Jeong et al, 21 with some modifications. In brief, frozen liver tissue (50 mg for mouse and 200 mg for rat) was hydrolyzed in 4 ml of 6 N HCl at 120 1C for 30 min.…”
Section: Hepatic Hydroxyprolin Contentmentioning
confidence: 99%
“…Silymarin also reduces the increase of hepatic stellate cells and TGF-1β production in the CCl 4 -treated rats suggesting that silymarin prevents hepatic fibrosis through suppression of inflammation and hypoxia in the hepatic fibrogenesis (44). Moreover, oral silymarin administration has been shown to reduce lipid peroxidation of brain tissues in acetaminophen induced toxicity by enhancing antioxidant enzymes (45).…”
Section: Discussionmentioning
confidence: 90%